PENGARUH METODE PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Fitrotul, Delia; Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The impact of role-playing training aided by audiovisual media on the academic performance of fourth-grade elementary school pupils in Civic Education is examined in this quasiexperimental study. Two fourth-grade classes from SDN Dukuh Kupang II Surabaya made up the sample; one class was The experimental group as well as the other was The group under control. A multiple-choice test consisting of ten items was used to gather data. The findings Of the self-sufficient samples T-Test revealed a statistically significant difference in the learning outcomes between the control and experimental groups, with a significance level of 0.000 (p < 0.05). The results indicate that fourth-grade elementary school students' academic performance in Civic Education is positively impacted by role-playing training supported by audiovisual materials.